2013
DOI: 10.1103/physrevb.87.035102
|View full text |Cite
|
Sign up to set email alerts
|

ω/Tscaling of the optical conductivity in strongly correlated layered cobalt oxide

Abstract: We report infrared spectroscopic properties of the strongly correlated layered cobalt oxide [BiBa0.66K0.36O2]CoO2. These measurements performed on single crystals allow us to determine the optical conductivity as a function of temperature. In addition to a large temperature dependent transfer of spectral weight, an unconventional low energy mode is found. We show that both its frequency and damping scale as the temperature itself. In fact, a basic analysis demonstrates that this mode fully scales onto a functi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
(58 reference statements)
1
2
0
Order By: Relevance
“…• An anomalous power-law dependence of the optical conductivity, σ(ω) ∼ 1/ω γ , over an extended range of frequencies, differing from conventional Drude behavior. This is observed in cuprates (Baraduc et al, 1996;El Azrak et al, 1994;Hwang et al, 2007;van der Marel et al, 2003;Schlesinger et al, 1990) and has also been reported in other materials (Dodge et al, 2000;Kostic et al, 1998;Limelette et al, 2013;Mena et al, 2003;Phanindra et al, 2018;Schwartz et al, 1998). This is also often accompanied by (ω/T )−scaling as a function of temperature, i.e.…”
Section: A Experimental Signatures Of Non-fermi Liquidssupporting
confidence: 62%
See 1 more Smart Citation
“…• An anomalous power-law dependence of the optical conductivity, σ(ω) ∼ 1/ω γ , over an extended range of frequencies, differing from conventional Drude behavior. This is observed in cuprates (Baraduc et al, 1996;El Azrak et al, 1994;Hwang et al, 2007;van der Marel et al, 2003;Schlesinger et al, 1990) and has also been reported in other materials (Dodge et al, 2000;Kostic et al, 1998;Limelette et al, 2013;Mena et al, 2003;Phanindra et al, 2018;Schwartz et al, 1998). This is also often accompanied by (ω/T )−scaling as a function of temperature, i.e.…”
Section: A Experimental Signatures Of Non-fermi Liquidssupporting
confidence: 62%
“…This is also often accompanied by (ω/T )−scaling as a function of temperature, i.e. σ(ω, T ) ∼ 1/ω γ F (ω/T ) (Lee et al, 2002b;Limelette et al, 2013;van der Marel et al, 2003;van der Marel et al, 2006). At higher energy or temperature, a transfer of spectral weight over energy scales larger (sometimes much larger) than k B T are also typically observed as temperature is varied (Basov et al, 2011;Georges et al, 1996;Rozenberg et al, 1996).…”
Section: A Experimental Signatures Of Non-fermi Liquidsmentioning
confidence: 97%
“…Nevertheless the distributions depend on the same dimensionless quantity E/T , where T is some effective parameter of dimension of energy, which is determined by electric field or acceleration correspondingly and by the integer parameter z. This indicates the new type of quantum criticality [33,34,35,36,37,38], emerging in the anisotropic vacua with z = 1. We will also discuss the opportunities to study these effects in the multilayer graphene experimentally.…”
Section: Introductionmentioning
confidence: 99%